Sustainable dam development in China between global norms and local practices - Oliver Hensengerth (Deutsches Institut für Entwicklungspolitik (DIE), 2010)
The paper explores reforms of China's environmental and resettlement policies and the influence of domestic and external actors on Chinese dam-related legislation. It also analyses the impact of these reforms on two dam projects: the Nu River Project and the Xiaolangdi Multipurpose Dam Project. The analysis starts with an overview of the strategic role of hydropower in the economic development plans of central and local government. This forms the context for domestic conflicts that ensue between economic planners and people affected by construction projects. The paper then analyses decision-making processes in the Chinese dam bureaucracy and the role allotted to civil society. By singling out two issue areas – Environmental Impact Assessment and resettlement – the paper examines legal changes and the reasons for them. The case studies then consider these processes, taking the Nu River Project as an example of using Environmental Impact Assessment and the Xiaolangdi Multipurpose Dam Project to illustrate resettlement.
Keywords: 330